UPAYA MENINGKATKAN PRESTASI BELAJAR IPA DENGAN METODE PEMBELAJARAN PENEMUAN (DISCOVERY) - Ngatono Ngatono (LPPM UNISDA, 2021)
The study aimed to know (1) the improvement of students achievement after applying the Discovery learning method, (2) the influence of the students achievement after applying the Discovery learning method. The study used classroom action research with three cycles. Each cycle consisted of four phases, those are planning, action and observation, reflection, and revision. The subject was the sixth graders of the odd semester at the first state senior high school Kranji, Paciran District, Lamongan Regency. The data collection was from the result of formative test, the observation sheet of teaching and learning activity. The analysis result showed that the students achievement has improved from the first cycle antil the third cycle, the first cycle (58,33%), the second cycle (75%), the third cycle (91,33%). The conclusion of the study was he discovery learning can give the positive influence to the students achievement on the Science lesson in the first state elementary school Kranji, Paciran District, Lamongan Regency.